Sensory characterization of vitis vinifera cv. Malbec wines from seven viticulture regions of Argentina - Goldner, María Cristina (2007)
Fil: Goldner, María Cristina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina